Statistic and Isotopic Characterization of Deep‐Sea Sediments in the Western North Pacific Ocean: Implications for Genesis of the Sediment Extremely Enriched in Rare Earth Elements. (16th July 2019) - Yasukawa, Kazutaka; Ohta, Junichiro; Miyazaki, Takashi; Vaglarov, Bogdan Stefanov; Chang, Qing; Ueki, Kenta; Toyama, Chiaki; Kimura, Jun‐Ichi; Tanaka, Erika; Nakamura, Kentaro; Fujinaga, Koichiro; Iijima, Koichi; et al.
Abstract: A certain type of deep‐sea sediment exhibits very high content of rare earth elements and yttrium (REY) and is therefore expected to serve as a novel resource for these industrially essential metals. In this paper, we statistically analyzed the bulk chemical composition of deep‐sea sediments collected from the western North Pacific Ocean. By applying independent component analysis to the multielemental data set, we extracted three independent components (ICs) that can be interpreted as the influence of Mn‐oxides (IC1), REY‐enriched biogenic calcium phosphate (IC2), and possibly a diagenetic effect involving Cu enrichment (IC3) on bulk sediment geochemistry. Subsequently, we selected representative samples based on the independent component analysis result, and implemented Sr–Nd–Pb isotopic analyses of bulk sediments. The results indicate that the extremely REY‐rich mud characterized by IC2 inherits the geochemical signature of deep Pacific seawater, whereas the non‐REY‐rich mud with less diagenetic alterations, characterized by IC3, implies an influence of terrigenous dust probably from the Taklimakan desert–Chinese loess plateau. IC1 may reflect the variation in sedimentation rates. Characteristic downhole variations of IC1 and IC3 scores imply the presence of hiatus and/or erosion of the sediment column across the REY content peak. The putative cause is an enhanced bottom current, which can physically separate coarse biogenic calcium phosphate grains with very high REY content and thus produce an extremely REY‐enriched sediment layer. Plain Language Summary: Recent studies discovered that deep‐sea sediment in the western North Pacific Ocean is remarkably enriched in rare earth elements that are essential for modern high‐tech products. These sediments are thus expected to serve as a new resource for these metals. However, the origin of such high concentrations of rare earth elements in the abyss is unclear. In this paper, we implemented statistical and isotopic analyses of these sediments, and discovered that they are characterized by three components: manganese oxides, biogenic calcium phosphates concentrating rare earth elements from seawater, and a chemical process that moves copper in the sediment. We suggest that a strong bottom current is the cause of a selective deposition of biogenic calcium phosphates that produces mud with an extreme enrichment in rare earth elements. Key Points: Multivariate analysis on geochemical data of deep‐sea sediments extracts key components associated with enrichment of rare earth elements Sr–Nd–Pb isotope analyses indicate systematic changes regarding sources of elements in the western North Pacific sediment Enhanced bottom current may cause significant enrichment of rare earth elements in the deep‐sea sediment